Gothic conventions as the ‘voice’ and representation of the inexpressible fear and trauma of racial oppression in the American South - Shireen Banu Mohammad Ebrahim Sahib (2014)
This essay illustrates how Gothic conventions represent the fear and trauma faced by the African-American community by providing an alternate reality for them to evoke their repressed memories.